MANAJEMEN GURU BIMBINGAN DAN KONSELING DI SMPN 1 BANDAR BARU KABUPATEN PIDIE JAYA - Nur Asiah, Murniati, Bahrun. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: Management guidance and counseling teacher is an important factor in the effort to realize the quality of educational institutions. Management guidance and counseling will be able to provide effective guidance services. This study aims to describe the program, implementation, evaluation, guidance and counseling teachers barriers in Junior High School (SMP) Negeri 1 Bandar Baru Pidie Jaya district. This research method is descriptive with qualitative approach. Collecting data using techniques: observation, interviews, and studies dokumensi. Subjects were Principal, Vice Principal, teacher guidance and counseling, as well as students. Data were analyzed by the technique: reduction, display, and verification. The results showed that: 1) Program guidance and counseling teacher made in the form of: annual program, the semester program, the program monthly, daily, and RPL has been arranged and documented; 2) Implementation of the guidance is implemented in accordance with a program that has priority. Preparation is done at the beginning of the year and involves counseling teacher, vice principal of student field, and coaches the student council. Implementation of the program in accordance with the problems faced by students; 3) Evaluation conducted adapted to cases resolved, including disciplinary offenses like coming late to school, do not use attributes schools, and brought HP to school. Evaluations are kualitatifa; and 4) Obstacles encountered, guidance and counseling teachers' lack of cooperation with the homeroom teacher, student council adviser in solving the problems of students.Keywords: Management, Teachers, Guidance and Counseling Abstrak: Manajemen guru bimbingan dan konseling merupakan faktor penting dalam upaya mewujudkan mutu lembaga pendidikan. Manajemen bimbingan dan konseling akan dapat memberikan layanan bimbingan yang efektif. Penelitian ini bertujuan untuk menggambarkan program, pelaksanaan, evaluasi, hambatan guru bimbingan dan konseling di Sekolah Menengah Pertama (SMP) Negeri 1 Bandar Baru Kabupaten Pidie Jaya. Metode penelitian ini bersifat deskriptif analitis dengan pendekatan kualitatif. Pengumpulan data menggunakan teknik: observasi, wawancara, dan studi dokumensi. Subjek penelitian adalah Kepala Sekolah, Wakil Kepala Sekolah, guru bimbingan dan konseling, serta siswa. Data yang diperoleh dianalisis dengan teknik: reduksi, display, dan verifikasi. Hasil penelitian menunjukkan bahwa: 1) Program guru bimbingan dan konseling yang dibuat berupa: program tahunan, program semester, program bulanan, harian, dan RPL telah tersusun dan terdokumentasi; 2) Pelaksanaan bimbingan dilaksanakan sesuai dengan program yang telah diprioritaskan. Penyusunan dilakukan pada awal tahun dan melibatkan guru bimbingan konseling, wakil kepala sekolah bidang kesiswaan, dan Pembina OSIS. Pelaksanaan program sesuai dengan permasalahan yang dihadapi siswa; 3) Evaluasi yang dilaksanakan disesuaikan dengan kasus yang diselesaikan, di antaranya pelanggaran disiplin seperti terlambat hadir ke sekolah, tidak menggunakan atribut sekolah, dan membawa HP ke sekolah. Evaluasi yang dilaksanakan bersifat kualitatifa; dan 4) Hambatan yang ditemui, guru bimbingan dan konseling kurangnya kerjasama dengan wali kelas, pembina OSIS dalam penyelesaian permasalahan siswa.Kata Kunci: Manajemen, Guru, Bimbingan dan Konseling